Stomach Content Analysis of Pangasius polyuranodon in Pinang Luar Lake Buluhcina Village, Siak Hulu Sub-Regency, Kampar Regency, Riau Province. - Herwandi, Zeldi; Windarti, Windarti; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPangasius polyuranodon is one of freshwater fish that live in the Pinang Luar Lake. This research aims to determine type of food present in the fishâ€™s stomach. This research was carried out in February-march 2020. Sampling was conducted once/week in the three times using nets. there were 58 fishes captured, but 2 of them had empty stomach and they cannot be used for stomach content analysis. The stomach content analysis using gravimetric method. Results show that the main food of pangasius polyuranodon in the Pinang Luar Lake is plants remaint (IP 90,40%), consist of plants (IP 86,55%), whole grains (IP 2,70%), remaining piece of woodÂ (IP 0,01%) and rind (IP 1,14%), while the animal remains (IP 9,6%) is consist of crustacean (IP 1,83%), meat (IP 0,31%), fish scales (IP 1,15%) and poultry (IP 6,31%). Based on data obtained, this fish categorized as omnivore.Keyword :Pangasius polyuranodon, Stomach Content Analysis, Gravim